Changes in the Construction of the Meaning of Beauty in the Perspective of Adolescent Girls in Padangsidimpuan City - Fitriani, Salwiyah; Fatmariza, Fatmariza (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This research is motivated by young women who do self-care to follow the beauty standards that apply to the current social construction in the city of Padangsidimpuan. The existence of this social construction has become a phenomenon among adolescent girls to force themselves to get a beautiful predicate from their environment so that teenagers who are in the stage of finding their identity position themselves to be following what society wants. The construction of beauty that is now embraced by teenagers has changed from time to time. The purpose of this study was to determine the changes in the shape of the construction of women's beauty in the city of Padangsidimpuan in the past and present. This research was conducted using a qualitative approach with a phenomenological study type. Determination of informants using a purposive sampling technique. Data was collected using observation, interviews, and documentation studies. Test the validity of the data using triangulation. The result is a change in the shape of the construction of the beauty of Padangsidimpuan women in the past and present which was built by the mass media and the public, who used to be sweet black women, broad legs and shoulders, black and thick hair, a body shape that is not thin and not fat is considered beautiful. experiencing various changes in the form of beauty with the criteria of having white facial skin, clean, without spots and acne, small legs, shoulders, and hands, slim body, tall and slender, and does not have other skin disorders. This study concludes that it must be realized that not all beauty standards need to be followed. Because the real beauty is women who can be themselves, be grateful for what they have by cultivating their senses, positive talents that they have for future success. Because by having a good heart, beauty can be perfect when combined with self-confidence that does not feel different from the prevailing beauty standards.